(untitled) (Baghdad Science Journal, 2012)
This research is dealing with five sample of tomato ketchup products available in local market that were respectively as follows: Hello-Baghdad Iraq, Tiffany-Abu Dhabi, Melody-Dubai, Baidar-Saudi Arabia, and Altunsa-Turkey. Also it is dealing with four sample of sauce products available in local market that were respectively as follows: Hello-Baghdad, Iraq, Al-Badawi-Baghdad Iraq, Family-Baghdad, Iraq, and Hala-Amman Jordon. Analysis was performed on each sample three times and mean of the reading was taking. Samples were tested through terse and shorthand from lengthened steps. The spectrophotometric method used rely on theoretical and practical bases in extraction and diagnosis by UV spectrophotometer. This method in short notes, consisted of achievement of extraction of the ketchup and sauce aqueous solution in three steps from which benzoic acid extracted in the form of benzoate, through these steps the benzoate form was changed into benzoic acid form, so the sample aqueous solution extracted using diethyl ether and its quantity was transferred by volume. The UV absorbance curve for benzoic acid was drawn in spectral range 200-290 nm, and the spectra for benzoic acid 250-290 nm was also drawn, whereas in this range the higher absorbance at 272 nm was predicted, and the final benzoic acid solution was tested using UV spect. at this proper wavelength, so the benzoic acid reading was obtained using acid standard curve utilization. In this work was also noticed that pH values for ketchup and sauce products are differed and ranging from 2 to 5 instead of the stated values that must be between 3.5 to 4.7. The higher recorded benzoic acid concentrations in ketchup samples in this work was higher as 1315 and lower as 745 mg/Kg, and it recorded a value 255 mg/Kg which approaches allowable value stated by Iraqi standardization (250 mg/Kg). Whereas the higher recorded benzoic acid concentrations in sauce samples in this work was higher as 2695 mg/Kg, and some of which recorded a value 280 mg/Kg which approaches allowable value stated by Iraqi standardization (250 mg/Kg). In general terms the concentration levels in samples investigated were higher than allowable value stated by Iraqi standardization (250 mg/Kg).